Determining factors influence self-efficacy on graduate leadership ability among university students in Zheng Zhou city - Peng, Ziqian; Khatibi, Ali; Tham, Jacquline (Edelweiss Applied Science and Technology, 2025)
With the deepening of economic globalisation and the constant changes in the external environment, the requirements for the quality of human resources are becoming higher and higher, and it has become a consensus that the process of globalisation requires leaders with a "global vision". Leadership, as a basic component of college students’ quality, is becoming increasingly important and has been highly valued by governments and organisations [1]. Social Science and Liberal Arts majors are more actively involved in student leadership. Student leaders do not have confidence in their leadership skills. They still lack leadership behaviours to bring exemplary impact to their organisations. The development of student-centred learning and the leadership behaviours of student leaders can complement each other. The adoption of student-centred learning can enhance student leadership behaviours [2].